Cutaneous manifestations of human immunodeficiency virus/acquired immunodeficiency syndrome: A comprehensive review - Daniel J Lewis; Steven R Feldman (Wolters Kluwer Medknow Publications, 2020)
Background: Cutaneous manifestations of human immunodeficiency virus (HIV) may be among the initial signs of HIV-related immunosuppression. As such, recognizing HIV-related cutaneous manifestations may lead to the early diagnosis of HIV infection, enabling the prompt initiation of antiretroviral therapy. Purpose: The objective of this article is to discuss the disease history, clinical findings, serologic findings, and treatment options of cutaneous manifestations of HIV. Methods: A nonsystematic review of the literature was performed using PubMed/MEDLINE and Scopus from which relevant articles were analyzed and summarized in the article. Results: There are a number of dermatologic conditions associated with HIV infection, which can be grouped into various categories: acute HIV infection, bacterial infections, viral infections, fungal infections, parasitic infections, papulosquamous dermatoses, eczematous dermatoses, and miscellaneous disorders. Skin-related disorders observed in HIV may result from the viral infection itself or from opportunistic infections or skin disorders secondary to the immunocompromised state inherent to the infection. Many associated skin diseases are more severe in HIV-infected patients, particularly those with severe immunosuppression as seen in acquired immunodeficiency syndrome. Conclusion: Prompt recognition of these skin manifestations is critical to the initiation of disease-modifying antiretroviral therapy.